If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 = 11a + -10a Combine like terms: 11a + -10a = 1a 6 = 1a Solving 6 = 1a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1a' to each side of the equation. 6 + -1a = 1a + -1a Combine like terms: 1a + -1a = 0 6 + -1a = 0 Add '-6' to each side of the equation. 6 + -6 + -1a = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -1a = 0 + -6 -1a = 0 + -6 Combine like terms: 0 + -6 = -6 -1a = -6 Divide each side by '-1'. a = 6 Simplifying a = 6
| 4x-20=-30 | | -6*-4+-.6666666667y+-4y=24 | | -3=1.25c | | -9p=12p | | 7x-12=8(x-9) | | -8x+24=-8(6+4x) | | 2(5x-5)=10(x-5) | | 3/20-4/5= | | 2a-11=-23 | | 5g+3(-4+3g)=1-g | | 5a^3-31a-28=0 | | 54x^3=6x | | v^2=-45-14v | | 0.5*y=14 | | -10b^2-(-9b^2-4)= | | 5(1-9a)=35 | | 3z+8+(-2z)=12 | | (x+2)*(x-6)-6=0 | | 2x^24=y | | 11k=264 | | 3/20-4/5-3/4= | | 2x+9=3(-7-2x) | | (kn)*m= | | 6a-9=15 | | -4+21a=10-2a | | 12+5(v)=2(v)-9 | | 14x+6=10+14x-4 | | 0.60x+0.60(60)=0.30(118) | | -9.2(x-3.5)=36.8 | | 2x^2+x^3y^4=1 | | 4(x-8)+7=11x-15 | | 3(6x+7)-9=18x+12 |